Photodynamic therapy in the complex treatment of trophic ulcers of venous etiology - B. V. Boldin; V. Yu. Bogachev; N. O. Somov; G. A. Varich; P. Yu. Golosnitskiy; K. V. Komov (Амбулаторная хирургия)
Introduction. In Russia, more than 5 million people suffer from venous ulcers. According to general studies, in more than 10% of cases, venous ulcers lead to permanent disability in patients. Currently, there is a growing interest in the use of photodynamic therapy (PDT), which has already proven its effectiveness in various fields of medicine.Aim. To improve treatment outcomes in patients with venous trophic ulcers by incorporating photodynamic therapy into complex treatment.Materials and methods. A prospective comparative study was conducted in 213 patients with CEAP C6. In the main group (n = 100), treatment was carried out using photodynamic therapy. The control group (n = 113) received standard treatment for venous ulcers.Results. The bacteriological study revealed significant statistical differences in the reduction in the level of bacterial contamination in patients of the main group compared to the control group. A comparison of the standard treatment of venous ulcers and the treatment method using PDT for the entire period of treatment showed that the use of PDT in the complex treatment of venous ulcers reduces the time for clearing ulcers by 1.75 times, accelerates the appearance of granulation tissue by 1.66 times, and accelerates healing by 1.87 times (p < 0.05).Discussion. The introduction of new medical technologies into clinical practice helps to improve the results of treatment of venous ulcers. The use of PDT in the treatment of venous ulcers has demonstrated high clinical effectiveness.Conclusion. The results of the study convincingly show that photodynamic therapy accelerates reparative processes in the ulcer, improves the state of the microbial background, and, accordingly, accelerates the rate of epithelization of the trophic ulcer.